PENGEMBANGAN MODEL PEMBINAAN SEKOLAH IMBAS ADIWIYATA BERBASIS PARTISIPASI - Sulistyowati, Ratih; Slameto, Slameto; Dwikurnaningsih, Yari (Universitas Kristen Satya Wacana, 2017)
The aim of this study is to see the shape of the model of impact school coaching management. This study is Research and Development (R & D). Data collection use interviewed, documentation, and Focus Group Discussion. The development phase is carried out through: (1) preliminary study, (2) arrangement model, (3) validation by expert from academic and also practitioner, (4) revision of product design and (5) proper model of coaching is tested. Data analysis conducted during in the field with the steps of data reduction, data display, and image/verification conclusions. The results showed that running coaching is difficult to finish. In addition, there is no structured and systematic planning, causing the implementation of coaching run by chance, depend on the demand from the school. There is no evaluation program for the coaching itself. The product of this study is coaching model Adiwiyata school impact base on participation that completed. Based on the feasibility result test conducted by experts and practitioners, the model is considered feasible to be tested by practitioners.